Scholars as European public intellectuals? Media interventions in the 2014 European Parliament election campaign. Issue 2 (15th March 2018) - Duller, Matthias; Korom, Philipp; Schögler, Rafael Y.; Fleck, Christian; ,
ABSTRACT: This paper presents results from a collaborative research project investigating European scholars from the social sciences and humanities (SSH) who acted as public intellectuals during the 2014 European Parliament (EP) election campaign. We analyze op-ed contributions published in 21 broadsheet newspapers and in 9 EU member states, written by 195 authors who contributed 262 articles. The result is a portrait of European SSH scholars acting as public intellectuals. It shows a clear overrepresentation of male authors of advanced age. Academic reputation and public prestige show an east–west divide, with prominent authors prevalently publishing in renowned "West European" newspapers. Disciplinary background offers the most noticeable differentiations. Political scientists are most active, however, predominantly publishing in domestic settings. By contrast, economists reach out to a wider international audience and write explicitly on EU matters, while intervening sociologists and philosophers, as the most senior intellectuals, examine Europe in its wider international and historical context. Correspondence analysis comprising the content of public interventions, and key characteristics of all contributors, suggests that even during the EU electoral campaign, scholars from the SSH do not necessarily contribute to the rise of a European public sphere, as their interventions are more domestic than European in focus.